2016
DOI: 10.3389/fendo.2016.00149
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D on Early Stages of Diabetic Kidney Disease: A Cross-sectional Study in Patients with Type 1 Diabetes Mellitus

Abstract: ContextGenetic and environmental factors are involved in the pathogenesis of type 1 diabetes mellitus (T1DM), and vitamin D (VD) deficiency appears as a candidate to risk factor for developing diabetic kidney disease (DKD).ObjectiveThe purpose of study was to evaluate the existence of an association between low levels of VD and the presence and degree of DKD in T1DM.Patients and methodsWe performed a cross-sectional study, between November 2014 and December 2015. Levels of 25(OH)D and albuminuria were analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 20 publications
1
24
0
Order By: Relevance
“…In addition, recently, we have compared T1DM subjects with controls and observed a progressive decline in VD levels/status as DKD worsened. Through linear regression analysis, we have suggested that a possible association between higher VD levels and lower values of microalbuminuria was independent of HbA1c and BP levels, hypothesizing a kidney direct effect of VD ( 18 ). Nonetheless, it is necessary to clarify how VD supplementation could bring improvements on this scenario.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recently, we have compared T1DM subjects with controls and observed a progressive decline in VD levels/status as DKD worsened. Through linear regression analysis, we have suggested that a possible association between higher VD levels and lower values of microalbuminuria was independent of HbA1c and BP levels, hypothesizing a kidney direct effect of VD ( 18 ). Nonetheless, it is necessary to clarify how VD supplementation could bring improvements on this scenario.…”
Section: Discussionmentioning
confidence: 99%
“…We performed a prospective study to evaluate the effect of vitamin D supplementation on CAN in T1DM patients as part of a research protocol (ISRCTN32601947) that has already provided evidence on other aspects of VD supplementation outcomes (17)(18)(19)(20).…”
Section: Study Design and Patientsmentioning
confidence: 99%
“…who reported that VDD correlated with eGFR and worsening renal function from stage 3–5 ( 38 ). In addition, other researchers reported that VDD can be associated with diabetic nephropathy in both type 1 and type 2 diabetes ( 39 , 40 ). Moreover, diabetic patients on hemodialysis have significantly lower levels of vitamin D than patients without diabetes ( 41 ).…”
Section: Discussionmentioning
confidence: 96%